INCLUSIVE TEACHER TRAINING AND ARTIFICIAL INTELLIGENCE: ETHICS, EMPATHY, AND DIGITAL NEURODIVERSITY - Cavalcante, Maryane Francisca Araujo de Freitas; Santos, Maisa Barbosa; D’Jesus Neta, Maria Raimunda; do Nascimento, Lucileide Aquino; Oliveira, Rildo da Silva; Santos, Francisco das Chagas Batista; Feitosa, Aryadynna Santos; Araújo, Luiz Melo; dos Reis , Leonilson Neri; da Rocha, Erimar Pereira; Cavalcante, João Gabriel Freitas; Lopes, Miranísia Aparecida de Araujo Freitas (Editora Impacto Científico, 2025)
This work is a brief theoretical and reflective overview, with a conceptual and interpretative character. The objective is to discuss and problematize the competencies necessary for inclusive teacher training in the age of Artificial Intelligence (AI), emphasizing inclusion and neurodiversity. Methodologically, it is a qualitative, exploratory, and bibliographic research, based on an integrative literature review (2020–2025) using Bardin's (2011) content analysis. The results indicate that technical mastery must be articulated with digital ethics and pedagogical empathy, allowing for personalization and accessibility for neurodivergent students. It is concluded that teacher training requires integration between technology and human sensitivity, preparing the teacher as an ethical agent and mediator of inclusive educational innovation.DOI: https://doi.org/10.56238/edimpacto2025.092-066